2023
DOI: 10.1002/sd.2652
|View full text |Cite
|
Sign up to set email alerts
|

Residential photovoltaic and energy storage systems for sustainable development: An economic analysis applied to incentive mechanisms

Idiano D'Adamo,
Alessandro Dell'Aguzzo,
Marco Pruckner

Abstract: The photovoltaic (PV) system has a very significant growing global trend and its role is essential in combating climate change. However, its intermittent nature requires integration with a battery energy storage system (BES). This work proposes an economic analysis based on net present value (NPV) for an integrated PV + BES system in a mature market (Italy). The analyses are applied to different policy (used for both PV and BES) and market (purchase price, selling price) contexts. Results show that the NPV(PV)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 75 publications
(118 reference statements)
0
4
0
Order By: Relevance
“…They concluded that replacing incentives for PV generation with a self-consumption bonus offers a return on investment in household energy storage systems equivalent to a capital subsidy on these systems and improves the cost-effectiveness when these systems are combined with PV. D'Adamo et al [35] argued that incentives based on tax deductions and subsidies for energy produced and self-consumed by PV generation systems integrated with storage systems can facilitate a sustainable energy future in the residential sector. The authors suggested a combination of policies: (i) subsidized tax deduction and rebate for generated and self-consumed energy for PV plants; (ii) subsidized tax deduction for battery-based storage systems at a lower value than PV plants; and (iii) promotion of the recycling industry.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They concluded that replacing incentives for PV generation with a self-consumption bonus offers a return on investment in household energy storage systems equivalent to a capital subsidy on these systems and improves the cost-effectiveness when these systems are combined with PV. D'Adamo et al [35] argued that incentives based on tax deductions and subsidies for energy produced and self-consumed by PV generation systems integrated with storage systems can facilitate a sustainable energy future in the residential sector. The authors suggested a combination of policies: (i) subsidized tax deduction and rebate for generated and self-consumed energy for PV plants; (ii) subsidized tax deduction for battery-based storage systems at a lower value than PV plants; and (iii) promotion of the recycling industry.…”
Section: Discussionmentioning
confidence: 99%
“…He studied in [40] the performance and economic benefits of adding BPA and Li ion battery systems to residential PV generation with different retail prices. Regarding the work carried out by the most relevant researchers on the subject, due to their number of publications and the fact that these are linked to the investment valuation of photovoltaic energy generation projects with storage, it was found that Idiano D'Adamo addressed in his publications the analysis and economic viability of photovoltaic systems with energy storage for the case of residences [29][30][31][32][33][34][35] and considered the impact of incentives and subsidies for these projects. The studies of this researcher were carried out in co-authorship with Massimo Gastaldi [33,34] and between Federica Cucchiella and Massimo Gastaldi [29][30][31]34].…”
Section: Analysis Of the Researchersmentioning
confidence: 99%
See 1 more Smart Citation
“…This system has numerous benefits, including the precision and dependability with which it generates power. Since grid-connected PV systems can cover the energy demands of multiple industries, they are becoming increasingly popular as power demand grows [8][9][10].…”
Section: Introduction 1general Overview Of Pv Grid-connected Systemsmentioning
confidence: 99%
“…The study in ref. [15] provides a feasibility analysis for the self‐consumption of these integrated systems in residences, thereby reducing reliance on the grid and offering greater financial returns for the user. Furthermore, it encompasses the combination of BESS with solar PV sources and suggests incentive policies, including a tax deduction of over 50% and a bonus for produced and self‐consumed energy in PV installations; a tax deduction for BESS, albeit at a lower rate compared to the PV system; and support for the recycling industry.…”
Section: Introductionmentioning
confidence: 99%